HUBUNGAN PERSEPSI COVID - 19 DENGAN PERILAKU MEROKOK PADA KELUARGA BINAAN FK UMSU - CUT SHANAZ DHIYA SHAFIRA; IKA NOPA (JURNAL ILMIAH SIMANTEK, 2021)
COVID-19 is a disease caused by SARS-CoV-2 infection. This virus has entered Indonesia since March 2020. The largeamount of information spread about COVID-19 has made the public have their own perception about COVID-19. Smoking isknown to be a risk factor for contracting COVID-19. To determine the relationship between the perception of COVID-19 andsmoking behavior in FK UMSU families. This research is a cross-sectional study. The research sample was taken using atotal sampling method, amounting to 33 people. The hypothesis test used is the Fisher Test which tests the data collectedbased on the COVID-19 Perception questionnaire and the smoking behavior questionnaire. The results showed that therewas a significant relationship between the perception of COVID-19 and smoking behavior (p value = 0.006). There is arelationship between the perception of COVID-19 and smoking behavior in FK UMSU assisted families.